Bone Mineral Density Loss in People With Epilepsy Taking Valproate as a Monotherapy: A Systematic Review and Meta-Analysis - Zhong, Rui; Chen, Qingling; Zhang, Xinyue; Li, Mengmeng; Liang, Jianmin; Lin, Weihong (Frontiers in Neurology, 2019)
Abstract Objective: Data on changes in bone mineral density (BMD) from valproate (VPA) therapy are ambiguous and conflicting. Thus, the aim of this study was to systematically review the existing data and carry out a meta-analysis to investigate the effect of VPA as a monotherapy on BMD in people with epilepsy (PWE). Methods: We systematically searched PubMed, EMBASE and MEDLINE for eligible studies. We calculated the standardized mean difference (SMD) with 95% confidence interval (CI) to investigate the statistical power of the association between VPA treatment and BMD. Results: Nineteen studies were included in this systematic review and meta-analysis. We found that BMD was lower in the VPA group than in the control group (SMD: -0.44; 95% CI: -0.65 to -0.22). A significant association was found in adult patients (SMD: -0.57; 95% CI: -0.88 to -0.26; I2=69.8%) and pediatric patients (SMD: -0.32; 95% CI: -0.60 to -0.03; I2=67.8%) by subgroup analysis. This study indicated that BMD was significantly lower in patients treated for more than 36 months than in controls (SMD: -0.52; 95% CI: -0.76 to -0.27; I2=61.8%). However, a significant difference was not found between patients who were treated for less than 36 months and controls (SMD: -0.36; 95% CI: -0.72 to 0.01; I2=74.8%). Conclusion and significance: The present study provided evidence that VPA treatment was significantly associated with BMD loss in PWE. Thus, for patients at a high risk of osteoporosis and fracture, especially for patients who need long-term treatment, VPA may not be a good choice.